Socio-demographic disparities in receipt of clinical health care services during the COVID-19 pandemic for Canadian children with disability - Gonzalez, Miriam; Zeidan, Jinan; Lai, Jonathan; Yusuf, Afiqah; Wright, Nicola; Steiman, Mandy; Karpur, Arun; Shih, Andy; Elsabbagh, Mayada; Shikako, Keiko (BMC health services research, 2022)
Background Little is known about the experience of receiving in-person and virtual clinical health care services during the COVID-19 pandemic for Canadian children with developmental disabilities and delays facing multiple layers of vulnerability (e.g., low income, low educational attainment families). We examined the relationship between socio-demographic factors and the receipt of these services (physical and mental health services) during COVID-19 for Canadian children with these conditions. Methods Data collected in Canada for the Global Report on Developmental Delays, Disorders and Disabilities were used. The survey: (1) was developed and disseminated in collaboration with caregivers of children with disabilities, (2) included topics such as response to the pandemic and receipt of services and supports, and (3) documented the experiences of a non-random convenience sample of caregivers of children (any age) with these conditions during and prior to the pandemic. We used four logistic regression models to assess the association between socio-demographic factors and receipt of services. Results Being a single parent, having low educational attainment (high school or less), having low income (making less than $40,000 per year), working less than full time (working part-time, working reduced hours due to COVID, retired, stay home parent or student), as well as male gender and older age of the child with disability were factors associated with decreased likelihood of receiving services. Conclusion Our findings point to the need for tailoring services for families of children with disabilities, particularly low socioeconomic status families, to ensure continuity of care during public health emergencies.